The phenomenon of non-adhesion sliding friction in conditions of boundary friction - Аксьонов, О.Ф.; Тернова, Т.В.; Стельмах, О.У.; Костюнік, Р.Є.; Сидоренко, О.Ю. (Proceedings of National Aviation University (archive), 2004)
For the first time it is proved experimentally the opportunity of realization the phenomenon of nonadhesion friction in conditions of boundary greasing. For research of realization this phenomenon in technics the new probing system of friction with an original technique of tests was developed and created.